Evaluation of Antidiabetic Properties of the Leaves Extract of Ficus vallis-choudae Delile in a Model of Type 2 Diabetes Induced by High-Fat Diet and Streptozotocin - Kilenma Kolefer; David Miaffo; Roger Ponka (The Scientific World Journal)
This work aimed to determine the phytochemical composition of the aqueous extract of leaves of Ficus vallis-choudae (AEFV) and to evaluate its antidiabetic properties on a model of type 2 diabetes induced by a high-fat diet (HFD) and a low dose of streptozotocin (STZ). The phytochemical analysis was carried out according to several methods using the standard of each bioactive compound. Type 2 diabetes was induced by feeding rats for 4 weeks with HFD lard followed by injection of a low dose of STZ (35 mg/kg). After induction, the rats were divided into groups and treated for 28 days with metformin (40 mg/kg) and the AEFV at doses of 110, 220, and 440 mg/kg. The results showed that the AEFV contains saponins, flavonoids, tannins, and total polyphenols. In addition, it dramatically reduced body mass, body mass index (BMI), atherogenic index (AI), coronary heart risk index (CRI), and abdominal fat and increased homeostatic model assessment of β-cell function (HOMA-β), high-density lipoprotein cholesterol (HDL-c) levels, and cardioprotective index (CI). The AEFV also lowered blood glucose levels, insulinemia, homeostatic model assessment of insulin resistance (HOMA-IR) index, and total cholesterol (TC), triglycerides (TG), low-density lipoproteins cholesterol (LDL-c), and very-low-density lipoproteins cholesterol (VLDL-c) levels. There was a decrease in alanine aminotransferase (ALT) and aspartate aminotransferase (AST) activity and in urea and serum creatinine levels following the administration of AEFV. The AEFV caused increased superoxide dismutase (SOD) and catalase (CAT) activities, reduced glutathione (GSH) levels, and decreased malondialdehyde (MDA) levels in the liver, kidneys, and heart of rats. The AEFV has hypoglycemic, antioxidant, and cardioprotective properties, thus validating its use in traditional medicine for the treatment of type 2 diabetes and its complications.